2013
DOI: 10.1097/mlr.0b013e3182894848
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Nursing and the Quality of Patient Care

Abstract: The body of evidence regarding linkages between nursing and quality of care has increased in the nature and depth of science between 2004 and 2009, as seen in higher rates and quality of publications, enhanced methodological rigor, and evidence of stronger interdisciplinary collaboration. Although the unique contribution of INQRI to this expanded body of knowledge is unclear, the evidence supports the increased importance of INQRI's goal of measuring and enhancing nursing's contributions to the quality of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…() reported trust is a pervasive influence on all aspects of therapeutic relationships, with service users feeling trust is essential to good service. Trust has also been described as an enhancer of the patient experience and linked to overall patient satisfaction (Naylor et al., ). In the UK, public perceptions of trust in nurses is higher amongst those who have had recent contact with a healthcare service, suggesting public trust in nursing is relational (The King's Fund, ).…”
Section: The Nature Of Trustmentioning
confidence: 99%
“…() reported trust is a pervasive influence on all aspects of therapeutic relationships, with service users feeling trust is essential to good service. Trust has also been described as an enhancer of the patient experience and linked to overall patient satisfaction (Naylor et al., ). In the UK, public perceptions of trust in nurses is higher amongst those who have had recent contact with a healthcare service, suggesting public trust in nursing is relational (The King's Fund, ).…”
Section: The Nature Of Trustmentioning
confidence: 99%
“…As reported by Naylor et al health status, quality of life, and patients’ or relatives’ experiences may be used to measure quality of nursing care in a health care setting [17]. However, in the ambulance services, there might be other measures that would capture the quality of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…the time at the scene may increase with a physician-based EMS, and a paramedic-based EMS may cause lack of proper pre-hospital airway management [15,16]. As for evaluation of nursing care, the findings from Naylor et al show that nursing care is both central and essential to the delivery of high quality care in different health care settings [17]. In the hospital setting, the result of Aiken et al showed a positive link between nurses’ educational level and decreased mortality rates and failure to rescue [18].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of nurses’ competence in ensuring patient safety has been confirmed in several studies (Finnbakk, Wangensteen, Skovdahl, & Fagerström, ; Kirwan, Matthews, & Scott, ; Needleman & Hassmiller, ), as well as its connections to healthcare quality (Naylor et al, ). Nevertheless, we could not identify studies that explore nurses’ competence in the newly established primary healthcare wards.…”
Section: Introductionmentioning
confidence: 89%
“…The development of the questionnaire was influenced by the validated questionnaire the Nurse Competence Scale (NCS) (Meretoja, Isoaho, & Leino-Kilpi, 2004 (Finnbakk et al, 2015). The questionnaire uses a 10-point numeric rating scale on the (a) and (b) items, respectively…”
Section: Data Collectionmentioning
confidence: 99%